PENGARUH E-COMMERCE, SELF EFFICACY DAN PENGGUNAAN SISTEM INFORMASI AKUNTANSI DALAM PENGAMBILAN KEPUTUSAN UNTUK BERWIRAUSAHA: Studi Kasus Pada Mahasiswa Program Studi Akuntansi Fakultas Ekonomi Universitas Flores - Ope, Martha Goreti; Ismail, Nuraini; Marselina, Apriana (Program Studi Akuntansi Universitas Flores, 2025)
This study aims to example whether there is an influence of E-Commerce, Self Afficacy and the Use of Accounting Information Systems in Making Decisions for Entrepreneurs (case study on accounting student at the faculty of economics, Universitas Flores). This research is a quantitative research. This study uses data collection techniques with questionnaires. This study used non-probability sampling with a purposive sampling technique with a total sample of 104 people, and used SPSS 25 as a research data processor. The results showed thet the E-Commerce variabel had a significant effect on the decision making for entrepreneurship for Accounting students at the Faculty of Economics, Universitas of Flores. This is evidenced by the regression coefficient value of the E-Commerce variable of 0,508 with t count>t table (4,092>1,983) with a significant level of 0,000<0,05, the Self Efficacy variable has a significant effect on Decision Making for Entrepreneurial Accounting Students at the Faculty of Economics, University of Flores. Hal this is evidenced by the value of the regression coefficient of the Self Efficacy variable of 0,393 with t count>t table (2,484>1,983) with a significant level of 0,015<0,05 and the variable use af accounting information systems has a significant effect on Decision Making for Entrepreneurial Accounting Students at the Faculty of Economics, University of Flores. This is evidenced by the regression coefficient value of the variables use of accounting information systems of 0,139 with t count>t table (1,527<1,983) with a significant level of 0,130>0,05.